Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas Ix Mts Nurul Jadid - Anik Marliana Ningsih; Shofia Hidayah; Susi Itawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve the mathematics learning outcomes of ninth-grade students of MTs Nurul Jadid by using the Problem-Based Learning (PBL) model. The type of research used is Classroom Action Research (CAR), which is carried out in two cycles. Each cycle includes the stages of planning, implementation, and reflection. The subjects of the study were ninth-grade students of Religion 2 in the first semester of the 2025/2026 academic year. Data were collected through observations of student and teacher activities, as well as learning outcome tests in each cycle. The study shows that the use of the Problem-Based Learning (PBL) model can improve student participation and learning outcomes. The average value increased from 69.35 before the intervention to 78.69 in the first cycle and 91.30 in the second cycle. The percentage of students who achieved learning objectives also increased from 52% to 90%. This increase indicates that PBL is effective in encouraging students to think critically, work together, and understand the concept of Linear Equations in Two Variables more deeply. Therefore, it can be concluded that the implementation of the Problem-Based Learning (PBL) model creates an active, meaningful, and student-centered mathematics learning environment, which has a positive impact on improving learning outcomes.